The prognostic value of pre-operative coronary evaluation in kidney transplanted patients - Steinmetz, Tali; Perl, Leor; Zvi, Benaya Rozen; Atamna, Mohamad; Kornowski, Ran; Shiyovich, Arthur; Hamdan, Ashraf; Nesher, Eviatar; Rahamimov, Ruth; Gal, Tuvia Ben; Skalsky, Keren (Frontiers in Cardiovascular Medicine, 2022)
Aims Non-invasive coronary assessment using single-photon emission computerized tomography (SPECT) testing for potential cardiac ischemia is an essential part of the evaluation of kidney transplant candidates. We aimed to examine the prognostic value of preoperative SPECT test results in kidney transplanted patients. Methods and results We retrospectively analyzed the pre-surgical nuclear SPECT test results in a registry of kidney transplanted patients. Follow-up at 1 month and 1 year recorded major adverse cardiac events (MACE) including non-fatal myocardial infarction, all-cause mortality and hospitalization due to cardiovascular disease following the renal transplantation. Of 577 patients available for analysis, 408 (70.9%) patients underwent nuclear SPECT test pre-transplant and 83 (20.3%) had abnormal results with either evidence of ischemia or infarct. A significantly higher incidence of post-operative MACE at 1 month was evident among patients with abnormal SPECT test compared to patients with no evidence of ischemia (10.8 vs. 4.3% respectively; P = 0.019). Differences were mostly derived from significantly increased rates of myocardial infarction events (8.4 vs. 1.8%; P = 0.002). Yet, MACE rate was not statistically different at 1 year (20.5 vs. 13.1%; P = 0.88). Importantly, the prognostic impact of an abnormal SPECT was significantly attenuated for all outcomes following multivariable adjusting for conventional cardiovascular risk factors and coronary revascularization. Conclusion Pre-surgical cardiac risk assessment of kidney transplant candidates with nuclear SPECT test was found to be predictive of post-operative MACE, yet apparently, its prognostic value was significantly attenuated when adjusted for cardiac risk factors.